Blood-Brain Barrier, Blood-Brain Tumor Barrier, and Fluorescence-Guided Neurosurgical Oncology: Delivering Optical Labels to Brain Tumors - Belykh, Evgenii; Shaffer, Kurt V.; Lin, Chaoqun; Byvaltsev, Vadim A.; Preul, Mark C.; Chen, Lukui (Frontiers in Oncology, 2020)
Because of aggressive growth, maximum safe resection of most gliomasis challenging for neurosurgeons. While recent advances have seen the introduction of a host of visualization techniques to complement intraoperative white light imaging of tumors, barriers to the effective use of these techniques within the central nervous system remain. In the healthy brain, the blood-brain barrier functions to ensure the stability of the sensitive internal environment of the brain, protecting the active functions of the central nervous system and preventing the invasion of microorganisms and toxins. Brain tumors, however, often cause degradation and dysfunction of this barrier, resulting in a heterogeneous increase in vascular permeability throughout the tumor mass and outside it. Thus, the characteristics of both of these barriers hinder the vascular delivery of a variety of therapeutic substances to brain tumors. Recent developments in the fluorescent visualization of brain tumors offer improvements in the extent of maximal safe resection, but many of these fluorescent agents must reach the tumor via the vasculature. As a result, these fluorescence-guided resection techniques are often limited by the extent of vascular permeability in tumor regions and fail to stain the full volume of tumor tissue. In this review, we describe the structure and function of both the blood-brain and blood-brain tumor barriers in the contextofthe current state of fluorescence-guidedimaging of brain tumors.With regard to fluorescent visualization techniques, we discuss the features of currently used techniques for fluorescence-guided brain tumor resection, with an emphasis on their interactions with the blood-brain and blood-tumor barriers. Finally, we discuss a selection of preclinical techniques that have potentialto enhance the delivery of therapeutics to brain tumors in spite of the barrier properties of the brain.